2016
DOI: 10.17159/sajs.2016/20140444
|View full text |Cite
|
Sign up to set email alerts
|

Urban farming as a possible source of trace metals in human diets

Abstract: HOW TO CITE:Olowoyo JO, Lion GN. Urban farming as a possible source of trace metals in human diets. S Afr J Sci. 2016;112(1/2), Art. #2014-0444, 6 pages. http://dx.doi.org/10. 17159/ sajs.2016/20140444 Rapid industrialisation and urbanisation have greatly increased the concentrations of trace metals as pollutants in the urban environment. These pollutants (trace metals) are more likely to have an adverse effect on peri-urban agriculture which is now becoming a permanent feature of the landscape of many urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…This process differs according to crop type, species, and plant parts (Säumel et al, 2012;von Hoffen and Säumel, 2014;Warming et al, 2015). We have found robust implemented urban EGI systems that takes into account trace metals can assist in counterbalancing external food resources (Chen et al, 2015;Olowoyo and Lion, 2016;Säumel et al, 2012).…”
Section: Egi and Urban Agriculturementioning
confidence: 99%
“…This process differs according to crop type, species, and plant parts (Säumel et al, 2012;von Hoffen and Säumel, 2014;Warming et al, 2015). We have found robust implemented urban EGI systems that takes into account trace metals can assist in counterbalancing external food resources (Chen et al, 2015;Olowoyo and Lion, 2016;Säumel et al, 2012).…”
Section: Egi and Urban Agriculturementioning
confidence: 99%
“…Pfister's [48] research observed a significant factor in the lack of response to an evacuation order in New South Wales, Australia, noting the effect of false alarms as a major factor that might make future evacuation more difficult if not impossible. In two studies, Olowu and Sako [49] and Olowoyo and Lion [50], looked at a number of developing countries including Nigeria, and found that limitation of infrastructure, absence of appropriate legal and policy framework and sometimes inadequate resources particularly render areas more vulnerable to the consequences of flooding and other natural disasters.…”
Section: Flood Predictionmentioning
confidence: 99%
“…Also, there is a need for more studies on other river catchments where there is lack of information in the Limpopo province. Other studies by Sibanda et al [25], Shibambu [32], Gumbo et al [68], and Olowoyo and Lion [69] have shown that the wastewater is rich in nutrients and essential traces such that the wastewater is usable for irrigation of crops, fruit trees, and vegetables. Limpopo province is a dry and arid region and the use of wastewater for irrigation is a welcome idea but there should be safeguards in place to protect the food consumers and irrigators from the negative impacts of wastewater reuse [68,69].…”
Section: Future Management Strategy Dealing Wastewater and Sludgementioning
confidence: 99%
“…Other studies by Sibanda et al [25], Shibambu [32], Gumbo et al [68], and Olowoyo and Lion [69] have shown that the wastewater is rich in nutrients and essential traces such that the wastewater is usable for irrigation of crops, fruit trees, and vegetables. Limpopo province is a dry and arid region and the use of wastewater for irrigation is a welcome idea but there should be safeguards in place to protect the food consumers and irrigators from the negative impacts of wastewater reuse [68,69]. The sludge may be used for innovative ways such as top soil cover (mined areas), biofertilizer, building materials, veld fire retardant and control, erosion control, forestry fertilization, and recovery of phosphorus [1].…”
Section: Future Management Strategy Dealing Wastewater and Sludgementioning
confidence: 99%